Yellow (577 nm) micropulse laser versus half-dose verteporfin photodynamic therapy in eyes with chronic central serous chorioretinopathy: Results of the Pan-American Collaborative Retina Study (PACORES) Group (2018)
Purpose To compare the functional and anatomical outcomes of eyes with chronic central serous chorioretinopathy treated with yellow micropulse (MP) laser versus half-dose verteporfin photodynamic therapy (PDT). Methods This is a multicentre, retrospective comparative study of 92 eyes treated with yellow MP laser (duty cycle of 5%, zero spacing between spots, spot size varied from 100 to 200 ?m, power varied from 320 to 660 mW, and the pulse burst duration was 200 ms) and 67 eyes treated with PDT (half-dose verteporfin (3 mg/m 2) infused over 10 min), followed by laser activation for 83 s. Spot sizes varied from 400 to 2000 ?m. Results In the MP group, at 12 months of follow-up, the mean best corrected visual acuity (BCVA) improved from the logarithm of the minimum angle of resolution (logMAR) of 0.41±0.27 at baseline to 0.21±0.26 (P less than 0.0001), 48.9% (45/92) of eyes had an improvement of ?3 lines of BCVA from baseline, 48.9% (45/92) of eyes remained within 2 lines of baseline BCVA, and only 2.2% (2/92) of eyes lost ?3 lines of BCVA from baseline. In the PDT group, at 12 months of follow-up, the mean BCVA changed from logMAR of 0.50±0.34 at baseline to 0.47±0.34 (P=0.89), 19% (13/67) of eyes had an improvement of ?3 lines of BCVA from baseline, 73% (49/67) of eyes remained within 2 lines of baseline BCVA, and 7% (5/67) of eyes lost ?3 lines of BCVA from baseline. There were no adverse events attributable to the yellow MP laser treatment. One eye in the PDT group developed choroidal neovascularisation, which was treated with three intravitreal bevacizumab injections. Conclusions Both PDT and MP are effective in restoring the macular anatomy. In places where PDT is not available, yellow MP laser may be an adequate treatment alternative. © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2018. All rights reserved. No commercial use is permitted unless otherwise expressly granted.